2023
DOI: 10.3390/socsci12070411
|View full text |Cite
|
Sign up to set email alerts
|

Can Children Learn How to Resist Repeated Leading Questions and Social Pressures?

Abstract: In forensic contexts, children who are victims or witnesses of crimes are repeatedly questioned using stressful leading questions and social pressure. The main aims of the present study are to verify the effects of repeated suggestive interviews on children’s level of suggestibility and resistant responses and to study how age and intelligence quotient may reduce the vulnerability of children. The study involved 110 children aged 10–15 years who were administered the Gudjonsson Suggestibility Scale 2, and 6 mo… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
14
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
4

Relationship

3
1

Authors

Journals

citations
Cited by 4 publications
(14 citation statements)
references
References 70 publications
0
14
0
Order By: Relevance
“…A previous pilot study with child participants was conducted to test the cue words used ( Vagni et al, 2023 ), and a good reliability index had been obtained (Cronbach’s alpha of 0.82). The lack of or poor response to some items suggested the replacement of some terms such as “Train” was changed to “Airplane.”…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…A previous pilot study with child participants was conducted to test the cue words used ( Vagni et al, 2023 ), and a good reliability index had been obtained (Cronbach’s alpha of 0.82). The lack of or poor response to some items suggested the replacement of some terms such as “Train” was changed to “Airplane.”…”
Section: Methodsmentioning
confidence: 99%
“…Numerous studies have shown that children are more vulnerable to suggestive questions and post-event information. Children also show a tendency to provide autobiographical memories that are poorer in detail and have a faster memory decay curve ( Goodman et al, 2002 ; Loftus, 2005 ; Bauer and Larkina, 2016 ; Gudjonsson et al, 2016 ; Vagni et al, 2023 ).…”
Section: Introductionmentioning
confidence: 99%
“…The increase in suggestibility appears to be due to a lack of source monitoring skills. As children grow, they develop greater source monitoring skills, managing to recognize misleading information and reject the suggestive questions [25].…”
Section: Introductionmentioning
confidence: 99%
“…Several factors can intervene to protect against the effects of repeated suggestive interviews, such as age [2], higher source monitoring skills [26] resilience skills [13,27,28], and memory confidence [4,5,29]. After the age of 12, children may develop a greater ability to reject suggestive questions even in cases of repeated interviews over time, although their significant vulnerability to socioemotional pressures and negative feedback remains [2,25,30].…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation